The Design of Student Service Information System to Print Grade Transcripts in the Industrial Engineering Study Program in Universitas Sebelas Maret Surakarta: Perancangan Sistem Informasi Pelayanan Mahasiswa Cetak Transkrip Nilai Di Program Studi Teknik Industri Universitas Sebelas Maret Surakarta - Hariyanto, Agus; Naury, Chairullah; Santosa, Eka Budhi (Politeknik Harapan Bangsa Surakarta, 2023)
The student service system at Universitas Sebelas Maret Surakarta (UNS), especially the print transcript of grades currently running, students can apply through three methods. The first method is done by filling out an application for a printed transcript. The second method is to use the Whatsapp application. The third method is done by using E-mail. Due to the large number of media used to apply for printed transcripts, the administrative unit of the study program cannot process all requests for print transcripts quickly. Sometimes there is a request to print a grade transcript that is not processed because the request data is overwritten with the new request data, so it is not readable by the study program administration unit. Based on the description of the background, it can be formulated that the problem to be solved in this research is